Fundamental analysis: stock valuation - Chateau, John Peter (My University, 2017)
To determine stock (market) price, threes approaches can be used: the wealth or patrimony approach, the comparative approach and the dynamic approach. Ponencia sobre los distintos enfoques alternativos que pueden ser utilizados en la valoración fundamental del patrimonio empresarial.
Keywords: Valoración; Valuation; Wealth